Study on Coupling Oscillation of Urban Rail Vehicle Traction System - Yan MU (机车电传动)
The DC power supply of urban rail vehicle was the key to good speed regulation performance of traction system. Limited by many factors such as on-board converter and harmonic suppression, the traction system was prone to DC side coupling oscillation under external excitation. By exploring the instability mechanism, the active and passive damping suppression methods were proposed, and the effectiveness and correctness of the oscillation suppression algorithm were verified by simulation. Thus, the DC side coupling oscillation suppression of traction system was realized.